An Empirical Analysis of Initial Public Offerings (IPO) Underpricing in Chinese A-share Market (2001-2015) - Sixian, Lin (2016)
Compare to other markets, Chinese stock market has extremely high level of IPO underpricing. This dissertation investigates the determinants of IPO underpricing on Chinese A-share market using a sample of 1376 IPOs listed during the period from 2001 to 2015. The study examines the applicability of traditional western theory on the Chinese IPO underpricing and also considers the specific characteristics of Chinese stock market when analysing the possible reasons for underpricing in China. The empirical results suggest that underwriter reputation theory, winner’s curse theory and ex-ante uncertainty theory are not applicable in China’s IPO market based on sample data. The principal-agent theory, time interval theory and signalling theory can explain Chinese IPO underpricing, although the test result of signalling theory is contrary to the expectation. Meanwhile, speculative bubble theory and information cascades theory have high explanatory power. More importantly, the study finds that application of equity separation reform and implementation of IPO reform in 2009 diminish the magnitude of underpricing. It can be concluded that the development of Chinese stock market indeed contributes to a gradually decline on underpricing level. However, the study finds that the adoption of book-building pricing mechanism intensifies the underpricing to some degree.